2010
DOI: 10.3109/08037051.2010.481816
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric septal hypertrophy – a marker of hypertension in aortic stenosis (a SEAS substudy)

Abstract: Hypertension is the main clinic characteristic of ASH and asymmetric LV hypertrophy in patients with asymptomatic aortic stenosis independent of severity of aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
1
23
1
1
Order By: Relevance
“…According to the recent American College of Cardiology Foundation/ American Heart Association guidelines, HCM is usually recognized by a regional increase in LV wall thickness ≥15.0 mm, with measurements of 13 and 14 mm considered borderline. 5 However, such asymmetrical wall thickening has also been described in both aortic stenosis and hypertension, [6][7][8] and we postulated that it might develop in response to strenuous physical training as well.…”
Section: Clinical Perspective On P 267mentioning
confidence: 82%
See 1 more Smart Citation
“…According to the recent American College of Cardiology Foundation/ American Heart Association guidelines, HCM is usually recognized by a regional increase in LV wall thickness ≥15.0 mm, with measurements of 13 and 14 mm considered borderline. 5 However, such asymmetrical wall thickening has also been described in both aortic stenosis and hypertension, [6][7][8] and we postulated that it might develop in response to strenuous physical training as well.…”
Section: Clinical Perspective On P 267mentioning
confidence: 82%
“…7,9 In brief, 541 consecutive healthy young white men army recruits were prospectively studied at entry to the British Army Training Regiment, Lichfield, United Kingdom, between July 2002 and April 2004. Recruits with an established diagnosis of hypertension, diabetes mellitus, cardiomyopathy, and those on regular medication were excluded.…”
Section: Study Recruitsmentioning
confidence: 99%
“…Furthermore, hypertension can be an aggravating factor in the progression of aortic stenosis, and its control is important to slow down the progression of valve disease 19 . Tuseth et al 20 found that hypertension is associated with a greater presence of asymmetric septal hypertrophy in patients with asymptomatic aortic stenosis, regardless of the severity of the stenosis, a condition that worsens the prognosis of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated whether these parameters could differentiate between normal controls and severe AS patients on the basis of the clinical knowledge that the LV response to aortic stenosis includes LV remodeling 23 , 24 , 25 , 26 , 27 , 28 . MATLAB R2013a (MathWorks, Natick, MA) was used to perform paired t ‐tests and a diagnostic classification test.…”
Section: Methodsmentioning
confidence: 99%